2017
DOI: 10.1590/s1678-9946201759053
|View full text |Cite
|
Sign up to set email alerts
|

Kidney involvement in malaria: an update

Abstract: Malaria is an infectious disease of great importance for Public Health, as it is the most prevalent endemic disease in the world, affecting millions of people living in tropical areas of the globe. Kidney involvement is relatively frequent in infections by P. falciparum and P. malariae, but has also been described in the infection by P. vivax. Kidney complications in malaria mainly occur due to hemodynamic dysfunction and immune response. Liver complications leading to hepatomegaly, jaundice and hepatic dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 24 publications
2
49
1
1
Order By: Relevance
“…Hemozoin pigment is known to be produced only by replicating parasites [16]. When in circulation, it is rapidly phagocytosed by macrophages and dendritic cells and therefore, has a short circulating half life [17,18] Hemozoin pigment in renal tissue has been demonstrated in the case of P. falciparum associated AKI [9]. Therefore, presence of hemozoin staining specifically in renal tubules and interstitiumis suggestive of the presence of replicating parasites at the site, rather than non specific accumulation of hemozoin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemozoin pigment is known to be produced only by replicating parasites [16]. When in circulation, it is rapidly phagocytosed by macrophages and dendritic cells and therefore, has a short circulating half life [17,18] Hemozoin pigment in renal tissue has been demonstrated in the case of P. falciparum associated AKI [9]. Therefore, presence of hemozoin staining specifically in renal tubules and interstitiumis suggestive of the presence of replicating parasites at the site, rather than non specific accumulation of hemozoin.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI), is a frequently presentation in severe malaria due to both P. falciparum and P. vivax, and more recently has also been shown to be associated with P. knowlesi [5][6][7][8]. In fact, overall AKI has been shown to have a global prevalence in about 20-50% hospitalized malaria cases [9]. Pathogenesis of P. falciparum is attributed to its cytoadherence to endothelial cells of tissue capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of the glomeruli and the increased thickness of the basement membrane have been described in other studies (7)(8)(9)(10) and attributed to the deposition of the malarial immune complexes (antigen, antibody and complement) (12,13) . It has been reported that the immune complex can be formed and localized in the glomeruli during human malaria (12)(13)(14)(15) resulting in the nephrotic syndrome (1,2) . The new and interesting observation as regards the pathological lesions in the kidneys is the evidence for degeneration of the proximal convoluted tubules (tubular nephrosis)…”
Section: Discussionmentioning
confidence: 99%
“…The usual consequences of malarial infection are tropical hepatosplenomegaly and nephrotic syndrome (1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI), is a frequent presentation in severe malaria which is associated with mortality [1][2][3][4][5]. Overall, AKI has been shown to have a global prevalence in about 20-50% hospitalized malaria cases [6,7]. While P. falciparum is found all over the tropical world, P. vivax is highly prevalent in South America, India and South East (S. E.) Asia, and P. knowlesi has been shown to cause malaria predominantly in S.E.…”
Section: Introductionmentioning
confidence: 99%